Enhancing firm performance through mutual respect and green compensation: The role of organizational culture as a moderating variable - Rahardika Bagaskara; Suharnomo Suharnomo; Mirwan Surya Perdhana (Diponegoro International Journal of Business, 2024)
In today's competitive and environmentally conscious business landscape, organizations are increasingly adopting green compensation systems to align employee incentives with sustainability goals. This study investigates the impact of the Green Compensation System, Organizational Culture, and Mutual Respect on firm performance using Structural Equation Modeling with Partial Least Squares (SEM PLS) for data analysis. The findings reveal that the Green Compensation System positively influences Mutual Respect, confirming the first hypothesis (H1). Additionally, a robust organizational culture significantly enhances firm performance, supporting the second hypothesis (H2). Furthermore, Mutual Respect significantly contributes to improved firm performance, validating the third hypothesis (H3). These results underscore the importance of integrating environmentally sustainable compensation programs, fostering a strong organizational culture through open communication, continuous training, and employee recognition. Moreover, strategies to enhance mutual respect among employees are essential. By adopting these recommendations, organizations can achieve superior performance and ensure long-term sustainability.